Association between apical periodontitis lesions and plasmatic levels of C‐reactive protein, interleukin 6 and fibrinogen in hypertensive patients. (20th November 2015) - Vidal, F.; Fontes, T. V.; Marques, T. V. F.; Gonçalves, L. S.
Abstract: Aim: To test the null hypothesis of association between chronic apical periodontitis (CAP) and plasmatic levels of the C‐reactive protein (CRP), interleukin‐6 (IL‐6) and fibrinogen in a population of severely hypertensive patients. Methodology: One hundred and seventy patients with severe refractory hypertension were selected. All patients were submitted to radiographic, clinical and periodontal evaluation. Plasmatic levels of CRP, IL‐6 and fibrinogen were measured on the morning of the first periodontal appointment using commercially available kits. Multiple linear regression analyses were carried out to appraise the effect of the co‐variables on the plasmatic levels of the inflammatory markers assessed. Results: Of the 170 subjects who participated, 105 (61.8%) were females and the median age of the participants was 53 years (range: 40–78). The adjusted multiple linear analyses demonstrated that plasmatic levels of CRP levels were associated with the body mass index (BMI) ( r = 0.259, P < 0.001) and residual tooth roots (RTR) ( r = 0.191, P = 0.041). IL‐6 and fibrinogen levels showed associated with BMI ( r = 0.400, P < 0.001 and r = 0.214, P = 0.002 respectively). CAP correlated weakly with CRP ( r = 0.250, P = 0.005), IL‐6 ( r = 0.174, P = 0.020) and fibrinogen ( r = 0.393, P < 0.001) levels. Conclusion: The null hypothesis was rejected in favour of the alternative hypothesis. In other words, the presence of chronic apical periodontitis was associated with higher plasmatic levels of CRP, IL‐6 and fibrinogen, in a population of severely hypertensive patients. However, the weak association between CAP and each dependent variable suggests a modest participation of endodontic infection on the plasmatic levels of biomarkers.